2020
DOI: 10.1016/j.ijid.2020.09.391
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and clinical characteristics of Clostridium difficile infection in Thailand

Abstract: Multivariable Cox regression showed patients with Genitourinary infection (HR: 2.23, p = 0.04) and Implantable devices (HR 11.30, p = 0.17) were at higher risk of death. Conclusion:The site-specific infection has shown to be a significant predictor of mortality in our study, these factors should be taken into consideration and needs further evaluation to understand their specific role in adverse outcome among a cohort of patients diagnosed with sepsis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Typically, this pathogen has been considered to be a problem in the western world, and thus, it has not been a priority in other places. However, new geographical areas such as Slovenia and Thailand are beginning to explore this pathogen from different environmental sources to understand the diversity that exists amongst the strains (Janezic et al 2016 , Putsathit et al 2017 , Imwattana et al 2020 , Tkalec et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typically, this pathogen has been considered to be a problem in the western world, and thus, it has not been a priority in other places. However, new geographical areas such as Slovenia and Thailand are beginning to explore this pathogen from different environmental sources to understand the diversity that exists amongst the strains (Janezic et al 2016 , Putsathit et al 2017 , Imwattana et al 2020 , Tkalec et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Majority of the isolates identified represent RTs (such as RT002, RT005, RT010, RT014/020, RT015, and RT023), which may suggest their association with humans and animals (Janezic et al 2016 , Tkalec et al 2020 ). The studies from Thailand focussed on clinical settings and reported prevalence of 9.2% and 15.6% ( n = 422) of toxigenic and nontoxigenic isolates, respectively, from the samples (Imwattana et al 2020 , Tkalec et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%